2000
DOI: 10.1038/sj.bjp.0703724
|View full text |Cite
|
Sign up to set email alerts
|

[Nphe1]‐Nociceptin (1‐13)‐NH2, a nociceptin receptor antagonist, reverses nociceptin‐induced spatial memory impairments in the Morris water maze task in rats

Abstract: 1 The present study was undertaken to investigate the e ects of the novel nociceptin receptor antagonist, [Nphe 1 ]-Nociceptin (1-13)-NH 2 (bilateral intrahippocampal injection, 50 nmole rat 71 ) on purported nociceptin-induced (bilateral intrahippocampal injection, 5 nmole rat 71 ) de®cits in spatial learning in the rat Morris water maze task. In addition, experiments were performed in an`open ®eld' to investigate possible peptide-induced changes in exploratory behaviour. 2 Nociceptin signi®cantly impaired th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…N/OFQ and its receptor are densely expressed in brain regions associated with learning and memory processes, such as the hippocampus, the amygdala, and the cerebral cortex (Darland and Grandy, 1998;Neal et al, 1999a,b). Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…N/OFQ and its receptor are densely expressed in brain regions associated with learning and memory processes, such as the hippocampus, the amygdala, and the cerebral cortex (Darland and Grandy, 1998;Neal et al, 1999a,b). Furthermore, NOP receptor activation with N/OFQ or synthetic agonists impairs memory performances in a variety of cognitive tasks in rodents (Sandin et al, 1997;Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Liu et al, 2007;Roozendaal et al, 2007), whereas the deletion of NOP receptor or preproN/OFQ gene produces the opposite effects (Manabe et al, 1998;Higgins et al, 2002;Mamiya et al, 2003). Consistent with these findings, electrophysiological studies showed that N/OFQ potently inhibits synaptic transmission and synaptic plasticity in the hippocampus and the amygdala (Yu et al, 1997;Meis and Pape, 1998;Yu and Xie, 1998;Wei and Xie, 1999; Bongsebandhu-phubhakdi and Manabe, 2007).…”
Section: Introductionsupporting
confidence: 70%
“…Previous studies have demonstrated the role of N/OFQ-NOP receptor system in working memory, spatial and fear learning (Hiramatsu and Inoue, 1999;Redrobe et al, 2000;Higgins et al, 2002;Mamiya et al, 2003;Sandin et al, 2004;Roozendaal et al, 2007), but the contribution of this novel neuropeptide system in modulation of recognition memory have not been investigated. Here, we show that intracerebroventricular infusion of N/OFQ or systemic administration of the selective NOP receptor agonist, Ro64-6198, impairs long-term object recognition memory formation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, OFQ/N has been shown to block LTP in hippocampal slices (Yu et al 1997) and impair spatial learning (Sandin et al 1997;Redrobe et al 2000) in rats. Furthermore, OFQ/N administration blocks morphine-induced conditioned place preference Ciccocioppo et al 2000) and tolerance (Lutfy et al 2001b), both of which rely on associative learning processes.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Moreover, exogenous nociceptin has been reported to impair learning and memory in intact mice 10,11 and in rats. 8,9 Here we investigated the mechanisms of nociceptin-induced modulation in learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…6 Owing to its structural similarity to classical opioids (68% homology with m receptor, 67% with d receptor, 66% with k receptor) and high density of ORL 1 receptors in the hippocampus, 7 it is of interest to explore whether nociceptin, like other opioids, modulates the synaptic plasticity and memory function in the hippocampus. Recent studies demonstrated that intrahippocampal 8,9 and intracerebroventricular 10,11 injections of nociceptin impair learning and memory in the water maze and passive avoidance tests, respectively. We have also reported that LTP in the hippocampal CA1 region and memory are facilitated in the ORL 1 receptor knockout mice compared to wild-type mice.…”
mentioning
confidence: 99%